The 5-aminolaevulinic acid-based photodynamic effects on nuclei and nucleoli of HL-60 leukemic granulocytic precursors - Smetana, K; Cajthamlová, H; Grebenová, D; Hrkal, Z (Journal of photochemistry and photobiology. B, Biology, 2000)
To provide more information on the 5-aminolaevulinic acid (ALA)-based photodynamic effect (PDE) on nuclei and nucleoli of individual leukemic cells, these structures were studied in cultured HL-60 cells which originated from leukemic highly immature and less differentiated precursors of granulocytes. The nuclear morphology was visualized by panoptic May-Grünwald/Giemsa staining and cytochemical method for DNA, nucleoli were visualized by cytochemical methods for the demonstration of RNA and silver stainable proteins including those of interphase silver stained nucleolus organizer regions (AgNORs). In most cells ALA-based photodynamic treatment (PDT) produced marked alterations such as formation of apoptotic bodies, and large condensation of nuclear chromatin structure but without nuclear segmentation. Such changes are in harmony with the apoptotic process induced in these cells but without previous terminal differentiation. In nucleoli ALA-based PDT produced the reduction and disappearance of nucleolar silver stainable particles (SSPs) representing AgNORs which apparently reflected the alteration of the nucleolar biosynthetic activity and cell proliferation. The latter is also reflected by the disappearance of mitotic divisions. On the other hand, a small subpopulation of cells was less sensitive or resistant to the ALA-based PDE since they did not show mentioned nuclear and nucleolar alterations.
Keywords: buněčné dělení; apoptóza; HL-60 buňky; kyselina aminolevulová; Apoptosis; Hematopoietic Stem Cells; Chromatin; Staining and Labeling; Cell Nucleolus; Eosine Yellowish-(YS); DNA; lidé; Cell Nucleus; Photochemotherapy; Photosensitizing Agents; RNA; barvení a značení; HL-60 Cells; Mitosis; fotosenzibilizující látky; mitóza; buněčné jádro; Methylene Blue; granulocyty; leukemie; chromatin; hematopoetické kmenové buňky; eosin; methylenová modř; Aminolevulinic Acid; Leukemia; Granulocytes; Cell Division; fotochemoterapie; buněčné jadérko; Humans